Autism and the transition to university from the student perspective. (August 2019) - Lambe, Sinead; Russell, Ailsa; Butler, Catherine; Fletcher, Sangeet; Ashwin, Chris; Brosnan, Mark
University provides individuals with the opportunity to develop greater independence in living skills and social networks, while also gaining valuable qualifications. Despite a high proportion of autistic individuals aspiring to attend university, many either do not seek or gain entry or drop out prematurely. Although some steps have been taken to develop effective support, a recent review highlighted the scarcity of research into programmes designed to support autistic students transitioning to university. In addition, few studies have examined the views of autistic students themselves. This study investigated the perspectives of autistic students transitioning to university. Three focus groups were conducted with 25 autistic students preparing to start university. Participants were asked about their hopes for starting university, as well as their worries and concerns. Data were analysed using thematic analysis, from which five main themes were identified: The Social World, Academic Demands, Practicalities of University Living, Leaving the Scaffolding of Home and Transition to Adulthood . The results provide an important account of the challenges autistic students face when transitioning to university, as well as their aspirations. These findings have a number of practical implications.